An ecological approach to discover new bioactive extracts and products: the case of extremophile plants. (26th April 2017) - Sahli, Ramla; Rivière, Céline; Neut, Christel; Bero, Joanne; Sahuc, Marie‐Emmanuelle; Smaoui, Abderrazak; Beaufay, Claire; Roumy, Vincent; Hennebelle, Thierry; Rouillé, Yves; Quetin‐Leclercq, Joëlle; Séron, Karin; et al.
Abstract: Objectives: Eight extremophile plants from Tunisia were screened to find natural products with benefits in human health. Methods: These plants were collected in different areas in Tunisia. Their methanolic extracts were evaluated for their total phenolic content and for their antiradical (DPPH), antimicrobial (on 35 bacteria and one yeast), antiviral (hepatitis C virus, HCV) and cytotoxic activity (against WI38 and J774 cell lines). The most active species were subjected to a bioguided fractionation. Key findings: The screening revealed promising activity for four plants, but two species have both antiradical and antimicrobial activity: Juncus maritimus and Limonium virgatum . The rhizomes extract of J. maritimus showed the highest activity against HCV, a selective antibacterial activity against Streptococcus dysgalactiae, and a moderate antiradical activity which is due to luteolin isolated in one step by centrifugal partition chromatography. The stems' and leaves' extracts of L. virgatum were rich in polyphenols responsible for the antiradical activity. Also, Limonium extracts showed an antibacterial activity with a broad spectrum. Conclusions: Extremophile plants have proven to be a promising source for bioactive metabolites. They have a powerful antioxidant system highly influenced by biotic and abiotic factors and the ability to produce secondary metabolites with antimicrobial activity.